Nystaleinae moths (Lepidoptera: Notodontidae): A morphological review of the subfamily - Prada-Lara, Liliana; Laurent, Ryan A. St; Weller, Susan; Fagua, Giovanny (Zootaxa, 2025)
Notodontidae, specifically the subfamily Nystaleinae, remains understudied despite its ecological and economic importance. This group, distributed exclusively in the Americas, was last revised almost 34 years ago. With a recent increase in the description of new genera and species, as well as a revised classification of the entire family, a revision of Nystaleinae is warranted. The traditional morphological classifications of notodontids have been challenged by recent phylogenomic evidence, that has revealed greater diversity within Nystaleinae than previously thought. Importantly, recent phylogenomic evidence suggests that the diverse subfamily of most diurnal species, the Dioptinae, is nested within Nystaleinae. And while Dioptinae has been fully revised recently, Nystaleinae sensu stricto has not. The need for an updated understanding of this diverse group is addressed in this work, which provides a morphological revision of the subfamily. Based on a literature review, curatorial work in biological collections, information available on online databases, and external and internal examination of specimens, the Nystaleinae s.s. is currently composed of 44 genera and 377 species, of which two are described herein: Falcicaputis St Laurent & Prada-Lara (with type species F. australis sp. nov., and further two species F. praxia (Schaus) comb. n. and F. modica (Dognin) comb. n.) and Pseudhippia St Laurent & Prada-Lara gen. n. for type species P. olivescens Schaus comb. n.). Based on our revised diagnoses, Lepasta brabilla Dognin, is recombined as Ankale brabilla comb, n., Gopha niveigutta Schaus is recombined as Poresta niveigutta comb. n., and Didugua albipuncta (Schaus) is recombined as Poresta albipuncta comb. n.. Descriptions, diagnoses, figures, distribution, valid species, and a pictorial/illustrated key to genus based on male terminalia is presented. Future research directions include unraveling the biogeography and evolutionary history of these moths in the New World, habitat preferences, phylogenetics analyses, and ecological studies. Avenues for further exploration, such as constructing phylogenetic trees, are outlined as vital steps toward confirming or refuting the morphological classification presented here.